Venturia inaequalis sensitivity to ergosterol biosynthesis inhibitors in Kashmir valley - and SABIHA ASHRAF, NASSREEN F. KACHO*, SABA BANDAY (Indian Phytopathology, 2013)
Monoconidial isolates of Venturia inaequalis were collected in 2006 and 2007 from apple orchards in Kashmir valley that had never been exposed or atleast treated with only 1-3 spray of fungitoxicants acting as ESBI. Sensitiveness of baseline and exposed isolates to two ESBIs hexaconazole and fenarimol were determined by a sensitivity test based on relative growth of mycelial colonies. For both fungitoxicants the population was constructed each with 240 monoconidial isolates. Baseline population were constructed with 90 monocondial isolates (30 from each orchard) for both fungitoxicants. The ED50 was determined for the baseline population which ranged from 0.0061 to 0.0233 Î¼g ml-1 with a combined value of 0.0135 Î¼g ml-1 for hexaconazole, while it ranged from 0.0284 to 0.0472 Î¼g ml-1 with a combined value of 0.0352 Î¼g ml-1 for fenarimol. For the combined population hexaconazole was 2.6 times more active than fenarimol. A discriminatory dose was selected close to ED50 values to test sensitivity of exposed population of 50 isolates from each orchards. The single discriminatory dose for hexaconazole and fenarimol were observed to be 0.02 and 0.05 Î¼g ml-1, respectively.